Perancangan User Interface Sistem Tata Kerja PT Kilang Pertamina Internasional Refinery Unit III - Larasati, Ratu Aprilia; Ruskan, Endang Lestari (INTERNAL (Information System Journal), 2024)
The evolution of information technology increasingly exerts significant influence across various life domains, including the business field. With this development, numerous companies and institutions are transitioning from manual systems to computerized systems. A prime example is PT Kilang Pertamina International Refinery Unit III, which possesses an integrated system enabling comprehensive corporate operational management. However, in reality, the Sistem Tata Kerja (STK) design remains non-computerized, still utilizing physical documents involving traditional procedural actions such as document creation, numbering, and authorization signatures by authorized leadership. Consequently, this frequently generates challenges, particularly during urgent document signature situations where leadership cannot be replaced by others. The research objective is to design a STK user interface utilizing Figma through prototyping method. The method used is prototyping, which consists of several stages, starting from Requirement Gathering and Analysis to the final stage, Implement Product and Maintain. The evaluation was conducted using the usability testing method with a tool called Maze. Based on the results, a score of 90 was obtained, indicating that the user interface is categorized into the high category. This demonstrates that the designed user interface can meet user needs while providing an efficient and user-friendly experience.